Serum Proteomic Analysis Identifies SAA1, FGA, SAP, and CETP as New Biomarkers for Eosinophilic Granulomatosis With Polyangiitis - Xiao, Jing; Lu, Shaohua; Wang, Xufei; Liang, Mengdi; Dong, Cong; Zhang, Xiaoxian; Qiu, Minzhi; Ou, Changxing; Zeng, Xiaoyin; Lan, Yanting; Hu, Longbo; Tan, Long; et al. (Frontiers in Immunology, 2022)
Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is characterized by asthma-like attacks in its early stage, which is easily misdiagnosed as severe-asthma. Therefore, new biomarkers for the early diagnosis of EGPA are needed, especially for differentiating the diagnosis of asthma. Objectives: To identify serum biomarkers that can be used for early diagnosis of EGPA and to distinguish EGPA from severe-asthma. Method: Data independent acquisition (DIA) analysis was performed to identify 45 healthy controls (HC), severe-asthma (S-A), and EGPA patients in a cohort to screen biomarkers for early diagnosis of EGPA and to differentiate asthma diagnosis. Subsequently, parallel reaction monitoring (PRM) analysis was applied to a validation cohort of 71 HC, S-A, and EGPA patients. Result: Four candidate biomarkers were identified from DIA and PRM analysis, i.e., serum amyloid A1 (SAA1), fibrinogen-α(FGA) and serum amyloid P component (SAP) were up-regulated in EGPA group, while Cholesteryl ester transfer protein (CETP) was down-regulated in EGPA group compared with S-A group. Receiver operating characteristics analysis show that, as biomarkers for early diagnosis of EGPA, the combination of SAA1, FGA and SAP have an area under the curve (AUC) of 0.947, the sensitivity of 82.35%, and specificity of 100%. The combination of SAA1, FGA, SAP, and CETP as biomarkers for differential diagnosis of asthma had an AUC of 0.921, the sensitivity of 78.13%, and specificity of 100%, which were all larger than single markers. Moreover, SAA1, FGA, SAP were positively, and CETP was negatively correlated with eosinophil count. Conclusion: DIA-PRM combined analysis screened and validated four previously unexplored but potentially useful biomarkers for early diagnosis of EGPA and differential diagnosis of asthma.